Activation of Notch Signaling During Ex Vivo Expansion Maintains Donor Muscle Cell Engraftment123. (20th September 2012) - Parker, Maura H.; Loretz, Carol; Tyler, Ashlee E.; Duddy, William J.; Hall, John K.; Olwin, Bradley B.; Bernstein, Irwin D.; Storb, Rainer; Tapscott, Stephen J.
Abstract: Transplantation of myogenic stem cells possesses great potential for long‐term repair of dystrophic muscle. However, a single donor muscle biopsy is unlikely to provide enough cells to effectively transplant the muscle mass of a patient affected by muscular dystrophy. Expansion of cells ex vivo using traditional culture techniques significantly reduces engraftment potential. We hypothesized that activation of Notch signaling during ex vivo expansion would maintain donor cell engraftment potential. In this study, we expanded freshly isolated canine muscle‐derived cells on tissue culture plates coated with Delta‐1 ext ‐IgG to activate Notch signaling or with human IgG as a control. A model of canine‐to‐murine xenotransplantation was used to quantitatively compare canine muscle cell engraftment and determine whether engrafted donor cells could function as satellite cells in vivo . We show that Delta‐1 ext ‐IgG inhibited differentiation of canine muscle‐derived cells and increased the level of genes normally expressed in myogenic precursors. Moreover, cells expanded on Delta‐1 ext ‐IgG resulted in a significant increase in the number of donor‐derived fibers, as compared to cells expanded on human IgG, reaching engraftment levels similar to freshly isolated cells. Importantly, cells expanded on Delta‐1 ext ‐IgG engrafted to the recipient satellite cell niche and contributed to further regeneration. A similar strategy of expanding human muscle‐derived cells on Notch ligand might facilitate engraftment and muscle regeneration for patients affected with muscular dystrophy. STEM Cells 2012;30:2212–2220